Ocean! : Our Watery World As You've Never Seen It Before - Derek Harvey; Nicola Temple; D. A. V. Stow; Andrew Beckett; Smithsonian Institution (New York : DK Publishing, 2020)
"Using 3-D computer illustrations that present a level of detail you simply can't find elsewhere, this book takes you on a world tour of the waters that cover 70 percent of our planet. You will see the fish, invertebrates, and other animals that call the ocean home and learn how their anatomy and behavior is adapted to deal with a watery habitat. You can discover what survives in the frozen Arctic Ocean, as well as see coral reefs teeming with life. Plus, you can find out the science of the seas: How do waves work? What are tsunamis? How do tides provide electricity? How can people help marine conservation?"--Amazon
Keywords: Instructional and educational works; Marine animals Juvenile literature; JUVENILE NONFICTION / Science & Nature / Earth Sciences / Water (Oceans, Lakes, etc.)